2015
DOI: 10.18632/oncotarget.4069
|View full text |Cite
|
Sign up to set email alerts
|

C/EBPα-p30 protein induces expression of the oncogenic long non-coding RNA UCA1 in acute myeloid leukemia

Abstract: Accumulating evidences indicate that different long non-coding RNAs (lncRNAs) might play a relevant role in tumorigenesis, with their expression and function already associated to cancer development and progression. CCAAT/enhancer-binding protein-α (CEBPA) is a critical regulator of myeloid differentiation whose inactivation contributes to the development of acute myeloid leukemia (AML). Mutations in C/EBPα occur in around 10% of AML cases, leading to the expression of a 30-kDa dominant negative isoform (C/EBP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(70 citation statements)
references
References 41 publications
1
69
0
Order By: Relevance
“…As non-coding RNA molecules in cells, lncRNAs participate in the regulation of multiple cell functions, such as cell proliferation, cell differentiation, cell migration and cell apoptosis [9]. Moreover, studies also demonstrate that lncRNAs play critical regulatory roles in a variety of disease processes, including neuro-degeneration and carcinogenesis [10,11] LncRNA urothelial carcinoma associated 1 (UCA1) has been aroused more and more attention in recent years due to its oncogenic/ tumor-suppressive roles in numerous cancer cells [12,13]. In terms of osteosarcoma, Li et al reported that overexpression of UCA1 promoted osteosarcoma initiation and progression [5].…”
Section: Introductionmentioning
confidence: 99%
“…As non-coding RNA molecules in cells, lncRNAs participate in the regulation of multiple cell functions, such as cell proliferation, cell differentiation, cell migration and cell apoptosis [9]. Moreover, studies also demonstrate that lncRNAs play critical regulatory roles in a variety of disease processes, including neuro-degeneration and carcinogenesis [10,11] LncRNA urothelial carcinoma associated 1 (UCA1) has been aroused more and more attention in recent years due to its oncogenic/ tumor-suppressive roles in numerous cancer cells [12,13]. In terms of osteosarcoma, Li et al reported that overexpression of UCA1 promoted osteosarcoma initiation and progression [5].…”
Section: Introductionmentioning
confidence: 99%
“…As lncRNAs have emerged as important participants in the pathogenesis and disease progression of AML, [66][67][68][69][70][71][72][73][74] it is likely that profiling of their expression would have significant impact on MDS prognostication. Recently, it has been shown that lncRNA expression signatures were closely associated with specific mutations and a small subset of lncRNAs could predict clinical outcome in cytogenetically normal elderly AML patients, 75 but the clinical significance of lncRNA profiling in MDSs has not yet been reported.…”
Section: Discussionmentioning
confidence: 99%
“…and repressed by C/EBPα and miR-1 (Hughes et al, 2015;Wang et al, 2014c;Wu et al, 2013;Xue et al, 2014). It has been described that HCV-induced reactive oxygen species (ROS) inhibit C/EBPα activity and stabilize the expression of HIF-1α (Miura et al, 2008;Nishina et al, 2008).…”
Section: Uca1 / Csr34mentioning
confidence: 99%